Modifications in Organic Acid Profiles During Fruit Development and Ripening: Correlation or Causation? - Batista-Silva, Willian; Nascimento, Vitor L.; Medeiros, David B.; Nunes-Nesi, Adriano; Ribeiro, Dimas M.; Zsögön, Agustín; Araújo, Wagner L. (Frontiers in Plant Science, 2018)
The pivotal role of phytohormones during fruit development and ripening is considered established knowledge in plant biology. Perhaps less well-known is the growing body of evidence suggesting that organic acids play a key function in plant development and, in particular, in fruit development, maturation and ripening. Here, we critically review the connection between organic acids and the development of both climacteric and non-climacteric fruits. By analyzing the metabolic content of different fruits during their ontogenetic trajectory, we noticed that the content of organic acids in the early stages of fruit development is directly related to the supply of substrates for respiratory processes. Although different organic acid species can be found during fruit development in general, it appears that citrate and malate play major roles in this process, as they accumulate on a broad range of climacteric and non-climacteric fruits. We further highlight the functional significance of changes in organic acid profile in fruits due to either the manipulation of fruit-specific genes or the use of fruit-specific promoters. Despite the complexity behind the fluctuation in organic acid content during fruit development and ripening, we extend our understanding on the importance of organic acids on fruit metabolism and the need to further boost future research. We suggest that engineering organic acid metabolism could improve both qualitative and quantitative traits of crop fruits.